클라이언트/서버 기반의 네트워크 게임 연구 - 변영기; 이한권; 김종겸; 조태경; Byun, Young-Ki; Lee, Han-Kwon; Kim, Jong-Gyeum; Cho, Tae-Kyung (전기학회 논문지 P권, 55(2), 2006)
A server is simply a computer that is running software that enables it to serve specific requests from other computers, called 'clients.' Distributed systems are considered by some to be the 'next wave' of computing. A collection of probably heterogeneous distribution systems is transparent to the user so that the system appears as one local machine. This paper is going to search about whole of Client/Server distributed systems environment through network game. This paper presents game by one example of network game. The ladder game uses JAVA and embody to do random every time using Random function and remainder operation repeatedly. Analyze execution principle of network game through this tame and investigate about Client/Server's distributed environment through this.